Pengujian Fitokimia dan Kadar Flavonoid Total Ekstrak Etanol Daun Bodhi (Ficus Religiosa Linn.) Serta Relevansinya Dengan Literatur Ayurveda - Ni Putu Sri Wahyuni; I Nyoman Piartha; Ni Made Sinarsari (UHN IGB Sugriwa Denpasar, 2022)
The development of the world of health with the use of drugs continues to increase by developing new biosyntheses from natural materials. One of the plants being explored was the bodhi plant (Ficus religiosa Linn.) through phytochemical testing and the total flavonoid content of ethanol extracts and their relevance to the Ayurvedic literature. This research uses Mixed Methods Sequential Exploratory Qualitative and Quantitative experimental laboratory with post test only control group design. The process of collecting data through observation, laboratory test results, and literature studies. Bodhi leaf samples were selected and determined for the experimental group. The initial stage is the extraction process using the maceration method using a technical 96% ethanol solvent. Next, phytochemical testing was carried out with the addition of reagents. Determination of total flavonoid content was carried out by the UV-vis spectrophotometer method using quercetin as the standard. The results of the phytochemical test showed that the ethanolic extract of the leaves of the bodhi plant was positive for bioactive alkaloids, flavonoids, and steroids, so further testing was carried out on total flavonoid levels and analyzed by linear regression equations with Microsoft office excel. The straight line equation shows that Y = 0.0064x – 0.0003 with a correlation coefficient (R2) of 0. 9825. The total flavonoid content is 13.61 ± 3.26 mg/g. Through this analysis, conventional medical uses or indications indicate that flavonoids are useful as antioxidants with their mechanism of counteracting free radicals so that they are effective as prevention and treatment of a disease. This is relevant when it comes to Ayurveda. Indications in Ayurveda state that the main indication of bodhhi is rejuvenation. This is also discussed in the Hindu religious book (Veda) called Rasayana tantra.